Indonesia : 2022 Article IV Consultation-Press Release; Staff Report; Staff Statement; and Statement by the Executive Director for Indonesia. (IMF Staff Country Reports; Country Report ;, 2022)
As elsewhere, the COVID-19 pandemic has led to tragic loss of life and triggered a major economic downturn in Indonesia. The authorities have responded with a bold and comprehensive policy package that has successfully maintained economic and financial stability. With the recovery underway, they have begun to withdraw the exceptional support measures. Nevertheless, the pandemic has caused scarring and reinforced the need to tackle longstanding structural challenges.